Production of Hydroxyapatite Recovery from Seashell Waste for Biomedical Application - Kang Siew Yi,; Janani K Yokesvaran,; ROSLEY, ROZAINITA (Multidisciplinary Applied Research and Innovation, 2024)
The extraction and purification of hydroxyapatite (HAp) from natural sources has been studied for several years to improve its quality and standard. Nowadays, it is used in various applications, especially for biomedical applications because of its bioresorbability, biocompatibility, and bioactive properties. Seashells contain a high composition of calcium carbonate which could be a promising source to extract HAp. In fact, the calcination process and wet slurry precipitation technique are the appropriate and simplest methods to produce hydroxyapatite from seashells. In this work, the effect of the reaction time of phosphate source, Potassium Dihydrogen Phosphate, ,  and calcium oxide,  on the production of hydroxyapatite was investigated. Production of HAp from seashell wastes can contribute significantly towards natural resource management, health care, waste utilization, and religious issues amongst others. Based on the results from X-ray diffraction (XRD), Fourier transform infrared spectrophotometer (FTIR), and scanning electron microscopy with energy dispersive (SEM /EDX), it is shown that HAp produced at 4 hours-reaction time is more crystalline compared to HAp produced at 2 hours and 3 hours-reaction time. It can be said that a crucial factor in the synthesis of HAp is reaction time.